1972
DOI: 10.1128/jvi.9.1.182-183.1972
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Reoxidation of Australia Antigen: Loss and Reconstitution of Particle Structure and Antigenicity

Abstract: Reduction of Australia antigen with dithiothreitol resulted in the loss of antigenicity and morphological integrity. Oxidation of the reduced Australia antigen reconstituted both of these characters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The SVPs are compact particles with a reported density of 1.21 g/mL in caesium chloride (CsCl) compared to a density of infectious virions between 1.24 and 1.26 g/mL [23,91,92]. The compact structure of the SVPs is due to the large number of intra-and inter-molecular disulfide bonds within and between the S-domains of the individual HBsAg subunits [62,65,90,[93][94][95]. Kinetic studies demonstrated that disulfide-linked HBsAgS dimers are formed in the ER, then the immature particle precursors are transported to a post-ER, pre-Golgi compartment, which excludes the enzyme "protein disulfide isomerase" and allows the formation of HBsAgS oligomers [96].…”
Section: Biochemical Properties Of Svpsmentioning
confidence: 99%
“…The SVPs are compact particles with a reported density of 1.21 g/mL in caesium chloride (CsCl) compared to a density of infectious virions between 1.24 and 1.26 g/mL [23,91,92]. The compact structure of the SVPs is due to the large number of intra-and inter-molecular disulfide bonds within and between the S-domains of the individual HBsAg subunits [62,65,90,[93][94][95]. Kinetic studies demonstrated that disulfide-linked HBsAgS dimers are formed in the ER, then the immature particle precursors are transported to a post-ER, pre-Golgi compartment, which excludes the enzyme "protein disulfide isomerase" and allows the formation of HBsAgS oligomers [96].…”
Section: Biochemical Properties Of Svpsmentioning
confidence: 99%
“…One lipoprotein particle contains ~100 HBsAg polypeptide monomers (Aggerbeck and Peterson, 1985;Ganem and Varmus, 1987;Peterson, 1987). I-IBsAg particles are unique among lipoproteins in that their structure is stabilized by extensive intermolecular disulphide crosslinking (Sukeno et al, 1972;Vyas et al, 1972;Imai et al, 1974;Peterson, 1987). It is the site of formation of these extensive crosslinks which is the subject of this paper.…”
mentioning
confidence: 94%
“…The envelope protein of hepatitis B virus (HBV), hepatitis B surface antigen (HBsAg), is a glycosylated lipoprotein usually shed in large amounts in the serum of infected individuals, where it is found as spherical particles with a diameter of 22 nm or filaments of similar diameter [for review, see Vyas et al, 19781. Alteration of conformation by reduction or detergent treatment [Sukeno et al, 1972;Vyas et al, 1972;Dreesman et al, 19731, greatly reduces the antigenicity of HBsAg, suggesting that its immunoreactivity is largely dependent on the spatial arrangement of distinct peptide regions that collectively constitute discontinuous epitopes [Benjamin et al, 19841. Serologically, HBsAg has a dominant epitope denoted a and two sets of subtype epitopes d or y [Le Bouvier, 19711 r [Bancroft et al, 19721, which historically have been generally believed to be mutually exclusive. Combinations of these epitopes thus give the four serotypes, adw, ayw, adr, and ayr.…”
Section: Introductionmentioning
confidence: 99%